Performance measurement analysis using the performance Prism and objective matrix: a case study of KPUD Tani Wilis - Harsys, Benaya; Iriani, Iriani (Universitas Mercu Buana, 2024)
Performance is one the critical aspect in every company or business that needs to be considered. However, a common issue encountered is that companies often fail to accurately assess their business performance. Inaccurate performance measurements result in a lack of continuous improvement in productivity and instead negatively impact the overall performance quality, thereby influencing revenue growth. This research focuses on key performance indicators (KPIs) that deviate from the standards set by KPUD 'Tani Wilis'. Consequently, alternative performance measurement approaches, such as identifying indicators using the performance Prism and evaluating performance through the objective matrix, are necessary. The results indicate that 68% of the indicators across various dimensions are in good condition, while 32% are below standard, with the required threshold set at 75% for good performance. The primary challenges identified include maintaining service quality for customers and ensuring supply delivery accuracy. The proposed solutions involve implementing robust control and monitoring systems focused on customer service quality, with dedicated supervisors or quality control experts overseeing the process.